ANALISIS PENGARUH WORKING CAPITAL TURNOVER, FIRM SIZE, GROWTH OPPORTUNITY DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PERUSAHAAN PT FAST FOOD INDONESIA TBK - Lilianti, Emma; Valianti, Reva Maria (Universitas Indo Global Mandiri Palembang, 2019)
This research purpose to analyze the effect of Working Capital Turnover, Firm Size, Growth Opportunity, Profitability on the Capital Structure of the Company PT Fast Food Indonesia Tbk. The year of observation for 5 years is 2014 at 2018, with the object of PT. Fast Food Indonesia Tbk. The method of analysis uses quantitative descriptive method. The results showed that the working capital turnover of the company> 3 times the efficiency of the company's working capital turnover in 2014 d. 2018 efficiency. The size of a good company can be seen from the company's total asset value quite well. Total assets of PT. Fast Food continues to experience a significant increase every year. Growth opportunity PT. Fast Food has decreased every year even though sales have increased. This shows the low growth opportunity of the company can mean that the company does not have flexibility in investing optimally because the company manager will take action to transfer wealth from creditors toinvestors, so that the company is expected to have low debt. The level of profitability can be measured from the level of the company's fluctuating profits and significantly increased in 2018. In 2014 to 2015 decreased by 4.7%, then in 2016 increased by 3.9% and in 2016 decreased by 1.37% and in 2018 experienced a drastic increase in profit of 5.55%.Keywords: Working Capital Turnover, Firm Size, Growth Opportunity, Profitability, Capital Structure